2020
DOI: 10.3390/agronomy10111717
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Organic and Conventional Management on the Rhizosphere Microbiome, Growth and Grain Quality Traits of Tritordeum

Abstract: Tritordeum is a novel hexaploid cereal derived from the cross between a wild Chilean barley species (Hordeum chilense Roem. et Schultz) and durum wheat (Triticum turgidum ssp. durum Desf.) that is potentially of great interest for human nutrition. In this study, a commercial and an experimental Tritordeum cultivar were analyzed in comparison with a reference durum wheat under conventional and organic management. We demonstrate that Tritordeum is better adapted to organic farming through an increase in the belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…All endophytic fungi isolated improved shoot growth and biomass of tomato plants, and some also exhibited activity that enhanced tomato fruit yields. Visioli et al found that Tritordeum cv., a novel hexaploid cereal, is more efficient at hiring beneficial microbes with plant growth promoting capacity like Bacteroides under organic management [ 82 ]. Similarly, Li et al found that under organic management, pepper plants recruit beneficial microbes more efficiently than under integrated or conventional management [ 78 ].…”
Section: Targeted and Untargeted Approaches To Soil Microbial Diversity Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…All endophytic fungi isolated improved shoot growth and biomass of tomato plants, and some also exhibited activity that enhanced tomato fruit yields. Visioli et al found that Tritordeum cv., a novel hexaploid cereal, is more efficient at hiring beneficial microbes with plant growth promoting capacity like Bacteroides under organic management [ 82 ]. Similarly, Li et al found that under organic management, pepper plants recruit beneficial microbes more efficiently than under integrated or conventional management [ 78 ].…”
Section: Targeted and Untargeted Approaches To Soil Microbial Diversity Managementmentioning
confidence: 99%
“…For instance, recent field research on the application of different soil microbial consortia to common wheat has highlighted heightened plant growth and nitrogen accumulation in the phases of stem elongation and heading, as well as upregulation of two gluten protein subunits, which are important indicators of flour quality [ 76 , 142 ]. Similarly, [ 82 ] demonstrated that the resilient cereal Tritordeum was better adapted to organic farming compared to conventional farming through an increased abundance of beneficial bacteria (Bacteroidetes) in the soil microbial community of the rhizosphere. The amount of minerals, gluten proteins and polyphenols increased in the grains too under this management, which would imply a link between belowground biodiversity and plant quality traits.…”
Section: Implications Of Soil Biodiversity For Nutrition and Food Safetymentioning
confidence: 99%
“…Tritordeum, including 'Bulel', seems better adapted to organic farming than durum wheat since it shows an increase in the below ground community of the Bacteroidetes phylum and better grain quality than durum wheat [17]. However, it has a lower grain yield [17].…”
Section: Progress In Breeding For Agronomic Performancementioning
confidence: 99%
“…Tritordeum, including 'Bulel', seems better adapted to organic farming than durum wheat since it shows an increase in the below ground community of the Bacteroidetes phylum and better grain quality than durum wheat [17]. However, it has a lower grain yield [17]. However, it is important to note that new advanced lines of tritordeum outperform 'Aucan' and 'Bulel' for yield performance [18].…”
Section: Progress In Breeding For Agronomic Performancementioning
confidence: 99%
“…A few recent studies in Europe have been focused on the agronomical traits, looking at yield performance of tritordeum cultivars (cvs) over conventional soft and durum wheats [7,12,13]. Scientific works have so far mainly focused on the bioactive compounds' content: tritordeum, in fact, has higher levels of carotenoids and arabinoxylans than wheat, and these result in a greater total antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%